HAMBATAN DALAM PENGEMBANGAN PROGRAM PARIWISATA BUDAYA DI PROVINIS NUSA TENGGARA TIMUR - Fransiskus Bustan; Alexander H. Kabelan; Christoforus D. Mata Rohi; Adryanus S. Toly Nau (Jurnal Lazuardi, 2020)
This paper provides the result of study exploring some barriers hampering the development program of cultural tourism in East Nusa Tenggara. The materials of this study were based on data collected through field and libary research. The result of the study shows that barriers hampering the development program of cultural tourism in East Nusa Tenggara are due to the lack of society’s undestanding on the esense of culture, the lack of society’s knowledge on the signifince of culture, the lack of society’s appreciation on their own culture. This paper might be beneficial to enrich the sources of reference for the government and the society of East Nusa Tenggara in developing the programs of cultural tourism.